High efficiency step-up converter using single switch with coupled inductors - Ali Hussein Al-Omari; Saif Al-Zubaidi (Institute of Advanced Engineering and Science, 2022)
Due to high demand for voltage boosting in the field of renewable energy sources, a novel topology of step-up converter with single switch is proposed in this paper. The converter uses single switch with coupled inductors architecture. The proposed topology enables to control the stepping-up gain by adjusting the duty cycle and selecting appropriate turn ratio of the coupled inductors. The two coupled inductors in the circuit can act as a step-up transformer. Moreover, the proposed technique aims to harness the turning off voltage stresses across the switching element and suppress the stress by transferring it to the load. The switching induced voltage was reduced by forwarding the power to charge a capacitor then transfer the power through a diode to the output. Circuit configuration, principles of operation and the gain transfer function of the converter are demonstrated. The proposed circuit is verified by comparing the practical results to the theoretical.